2018
DOI: 10.4168/aair.2018.10.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infections and Associated Factors That Promote Acute Exacerbations of Asthma

Abstract: Despite asthma being the most common chronic childhood ailment, there is still much to learn about the disease. Early childhood infections with well-known or emerging viruses can lay the pathophysiologic framework for asthma development and exacerbation later in life, which may be due partly to alteration of the airway microbiome. Once asthma is established, acute exacerbations are usually associated with infections with respiratory viruses, such as rhinoviruses (RVs). Once again, there are bidirectional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 67 publications
(73 reference statements)
0
36
0
Order By: Relevance
“…The major cause of asthma exacerbations is respiratory infection with rhinovirus (RV) accounting for up to 80% of all exacerbations (8). Viral-induced exacerbations in asthma are associated with increased levels of interleukin (IL)-6, the neutrophil chemoattractant CXCL8 and neutrophilic inflammation (9,10). There are some studies that have reported bacterial infection to also be related to asthma exacerbations (11,12), however this relationship is less evident.…”
Section: Introductionmentioning
confidence: 99%
“…The major cause of asthma exacerbations is respiratory infection with rhinovirus (RV) accounting for up to 80% of all exacerbations (8). Viral-induced exacerbations in asthma are associated with increased levels of interleukin (IL)-6, the neutrophil chemoattractant CXCL8 and neutrophilic inflammation (9,10). There are some studies that have reported bacterial infection to also be related to asthma exacerbations (11,12), however this relationship is less evident.…”
Section: Introductionmentioning
confidence: 99%
“…As rhinovirus is known to be the main cause of acute asthma exacerbations, rhinovirus was unsurprisingly detected in the majority of our subjects . The EBT is known to increase with viral infections .…”
Section: Discussionmentioning
confidence: 81%
“…20,22 As rhinovirus is known to be the main cause of acute asthma exacerbations, rhinovirus was unsurprisingly detected in the majority of our subjects. [29][30][31] The EBT is known to increase with viral infections. 6 However, we did not detect a difference in the PLET between virally infected children and those without evidence of a viral illness.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in this study were also tested for virus infection as it is well known that respiratory viral infection is the major cause of asthma exacerbation in children. 27 We detected virus in about half of the treated subjects and reduction in sEDN levels was significantly larger in the virus-negative subgroup of the MONT group, indicating that virus infection may have hindered the effect of montelukast ( Supplementary Fig. S1 ).…”
Section: Discussionmentioning
confidence: 87%